Biodegradation of pyrene and phenanthrene by bacterial consortium and evaluation of role of surfactant - Kumari, B.; Rajput, S.; Gaur, P.; Singh, S. N.; Singh, D. P. (Cellular and Molecular Biology, 2014)
High molecular weight poly aromatic hydrocarbons (HMW PAHs) are well known for their hydrophobicity and they get strongly adsorbed onto the soil particles. Generally, surfactants facilitate the biodegradation of PAH by enhancing their solubility and desorption of hydrophobic compounds from soil particles. To investigate the role of synthetic surfactant in biodegradation of PAHs, two bacterial strains BP10 and P2 were incubated in soil spiked with pyrene and phenantherene (100 Î¼g g-1of soil each) in isolation and in combination with/without Tween 80. After 14 days of incubation, pyrene and phenantherene were degraded by a combination of BP10 and P2 to the extent of 98% and 99%, respectively. Addition of tween 80 reduced the degradation of pyrene and phenantherene by 35 and 10%, respectively. Biosurfactant produced by selected strains i.e. BP10 and P2 could enhance desorption of pyrene (100 Î¼g g-1of soil) by about 27% and 12%, respectively. However, desorption activity was relatively higher (32 and 29%, respectively) in case of phenanthrene (100 Î¼g g-1of soil) from the spiked soil. Present study showed that in spite of additional chemical surfactant, bioaugmentation of highly petroleum hydrocarbon degrading bacterial combination was very effective in boosting the bioremediation of PAHs- contaminated sites.